2019
DOI: 10.1155/2019/4096847
|View full text |Cite
|
Sign up to set email alerts
|

sFlt-1/PlGF Ratio as a Predictive Marker in Women with Suspected Preeclampsia: An Economic Evaluation from a Swiss Perspective

Abstract: In Switzerland, 2.3% of pregnant women develop preeclampsia. Quantification of the soluble fms-like tyrosine kinase-1 (sFlt-1) and placental growth factor (PlGF) ratio has shown a diagnostic value in the second and third trimesters of pregnancy, in particular in ruling out preeclampsia within one week. We estimated the economic impact of implementing sFlt-1/PlGF ratio evaluation, in addition to the standard of care (SOC), for women with suspected preeclampsia from a Swiss healthcare system’s perspective. A dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
2
16
0
8
Order By: Relevance
“…Among them, imbalance release of sFlt1 and PlGF plays critical roles in PE development 3,4 . Many studies have shown that sFlt1/PlGF ratio is markedly increased in PE patients and in women with pre‐existing conditions predisposing or mimicking PE 43–46 . In consistence with these studies, we demonstrated that an increased circulatory sFlt1/PlGF ratio was found in the rats with PE‐like features induced by placental 11β‐HSD2 downregulation.…”
Section: Discussionsupporting
confidence: 83%
“…Among them, imbalance release of sFlt1 and PlGF plays critical roles in PE development 3,4 . Many studies have shown that sFlt1/PlGF ratio is markedly increased in PE patients and in women with pre‐existing conditions predisposing or mimicking PE 43–46 . In consistence with these studies, we demonstrated that an increased circulatory sFlt1/PlGF ratio was found in the rats with PE‐like features induced by placental 11β‐HSD2 downregulation.…”
Section: Discussionsupporting
confidence: 83%
“…Analysis of the economic impact in the UK indicated that hospitalizations of women with suspected preeclampsia were reduced by 56%, resulting in net savings of £344 per patient for the healthcare provider [28]. The substantial cost saving results per patient were replicated in Italy (€670) [25], Germany (€361) [27], Brazil (R $185-636) [24], Switzerland (€346) [26], and the US ($1,215) [29]. Taken together, these studies show that the sFlt-1/PlGF ratio test yields cost savings for different populations/geographical areas and from the perspective of a range of healthcare providers with different procedures and financial models.…”
Section: Discussionmentioning
confidence: 99%
“…PlGF, placental growth factor; PROGNOSIS, PRediction of short-term Outcomes in preGNant wOmen with Suspected preeclampsIa Study; sFlt-1, soluble fms-like tyrosine kinase-1 addition to its clinical performance. Similar research on the cost analysis of introducing the sFlt-1/PlGF ratio test has been performed using population-level data from PROG-NOSIS in the UK, Italy, Germany, Brazil, Switzerland, and the US [24][25][26][27][28][29][30]. In PROGNOSIS, the sFlt-1/PlGF ratio has been shown to improve the short-term prediction of preeclampsia in women with clinical suspicion of the condition, and NICE guidelines recommend the use of the sFlt-1/ PlGF ratio test to rule out preeclampsia, in addition to standard care, in women between 20 and 34 weeks + 6 days of gestation [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is characterized by the imbalance between the generation of reactive oxygen species (ROS) and the antioxidant defence system, [ 9 , 10 ]. ROS can induce placental dysfunction by suppression of placental angiogenesis, induction endothelial damage, and immune malfunction, which are suggested to be the underlying of PE development [ 11 13 ]. Several studies have found suppressing oxidative stress, and scavenging ROS represents potential therapeutic opportunities for the treatment of PE development [ 11 ] [ 14 ].…”
Section: Introductionmentioning
confidence: 99%